2016
DOI: 10.1155/2016/9612856
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Influence of DPF Micropore Structure and Particle Property on Its Filtration Process

Abstract: A single layer filtration system was developed to investigate the filtration and regeneration performance of diesel particle filter (DPF). The particle layer thickness was directly measured online to analyze the different filtration stages. The influence of particle property on particle layer stage performance was also investigated. The results indicate that the filtration velocity can greatly affect the deep bed filtration stage, and the deposited particle layer can be compressed even in very low filtration v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…One of the most important parameters to characterize the pore network is the pore size distribution, which can be experimentally measured through mercury intrusion porosimetry . It was found that pore size distributions of particulate filters from porosimetry measurements can be fitted using a log-normal distribution function. ,, On the basis of a recently developed PDF-based statistical approach, a single piece of porous cell is represented by a cluster of spherical collectors, which is modeled by a log-normal distribution function as shown in Figure . In each cell, the total filtration efficiency is calculated as the sum of PDF weighted contributions from all of the collectors with distinct diameters where l dc is a length scale that represents the overall filter collector size and is defined as l dc = [∫PDF d ci · d ci 2 · d ( d ci )] 1/2 .…”
Section: Multiscale Filtration Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the most important parameters to characterize the pore network is the pore size distribution, which can be experimentally measured through mercury intrusion porosimetry . It was found that pore size distributions of particulate filters from porosimetry measurements can be fitted using a log-normal distribution function. ,, On the basis of a recently developed PDF-based statistical approach, a single piece of porous cell is represented by a cluster of spherical collectors, which is modeled by a log-normal distribution function as shown in Figure . In each cell, the total filtration efficiency is calculated as the sum of PDF weighted contributions from all of the collectors with distinct diameters where l dc is a length scale that represents the overall filter collector size and is defined as l dc = [∫PDF d ci · d ci 2 · d ( d ci )] 1/2 .…”
Section: Multiscale Filtration Modelingmentioning
confidence: 99%
“…Furthermore, the porosity distribution across the filter wall was found to have a significant effect on local flow distribution, filtration efficiency, and pressure drop. 26,53,54 Our previous simulation studies 25 showed that most of particles were deposited at the top slab with a constant or homogeneous porosity, resulting in a high particle concentration gradient near the top surface of the substrate. With an inhomogeneous porosity distribution, the highest concentration of particles was observed at the transition region of the porosity distribution rather than at the top slab.…”
Section: ■ Multiscale Filtration Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…The nature of the actual ship-emitted black carbon is closely related to the engine type, size, fuel composition, and operational conditions. Studies by Meng et al, Boger et al, Pfau et al, and other researchers suggest that considering carbon black, notably Printex-U carbon black, as a viable substitute for black carbon (BC) is plausible, particularly in the context of diesel soot exhibiting similar physical traits and featuring high elemental carbon content. This research plays a vital role in the development of ship-based BC emission control.…”
Section: Introductionmentioning
confidence: 99%